Phenomenological description of coherent radar images based on concepts of the measure on a set and stochastic integral - Volosyuk, V.K.; Zhyla, S.S.; Kolesnikov, D.V. (Radiotekhnika, 2018)
The model of scattered electromagnetic fields in the region of their receiving for solving problems of the Earth remote sensing is proposed, using a phenomenological approach based on the laws of geometrical optics and the Huygens-Fresnel principle. The procedure for their processing, while restoring a coherent radar image of the earth's surface in the near Fresnel zone, is shown. The structure of the obtained image is described by the convolution integral of the complex scattering coefficient with the radar system ambiguity function. It is noted that, due to the complex internal structure of the scattering coefficient, it is reasonable to consider the field in the receiving region not only as Riemann integrals, but also Lebesgue and Stieltjes integrals, and Ito stochastic integrals.